Andre Delbecq a leader's leader and master mentor - Weiss, Joseph W. (2020)
This is a tribute to Andre Delbecq in memory of his contributions as a master mentor, teacher, consultant, and innovator in spirituality and leadership - as written through the lens of our relationship and shared journey spanning four decades. As a PhD student at the University of Wisconsin, Madison to a Professor of Management at Bentley University in Waltham, MA, I personally and professionally experienced and benefitted from Andre's gifts as he evolved from eminent scholar/professor, consultant, and friend, to an acknowledged Spiritual Director. This article may also serve as a small portal through which to glimpse some of the effects Andre still has on so many.
Keywords: Andre Delbecq; Mentor; leaders' leader; Leadership; Mindfulness; Spirituality; Mentor; leaders' leader; Andre Delbecq; Leadership; Spirituality; Mindfulness; Aufsatz in Zeitschrift